The NUCKS1-SKP2-p21/p27 axis controls S phase entry - Samuel Hume (Nature Portfolio, 2021)
Entry into S phase of the cell cycle is regulated positively by mitogens and negatively by DNA damage; however, how balance of these signals is achieved is not well known. Here the authors show that the NUCKS1-SKP2- p21/p27 axis integrates this information, where the NUCKS1 transcription factor affects levels of p21/p27 to readout the mitogen:DNA damage balance and regulate S phase entry decision.